Comparison of Health Cadre's Knowledge Regarding Stunting Prevention in Lowland and Highland - Saputri, Melisa Fitria; Widiasih, Restuning; Khoirunnisa, Khoirunnisa (GLOBAL HEALTH SCIENCE GROUP, 2024)
On 2022, the incidence of stunting stilll exceed the target recommended by World Health Organization (WHO). Efforts to prevent stunting require the involvement of all parties in society, including health cadres and their knowledge about stunting prevention. The purpose of this research was to compare the level of knowledge of health cadres on stunting prevention between lowland and highland villages in Pangandaran. This research design used a descriptive comparative with a cross sectional time. The population in this study are health cadres in Karangjaladri village and Cimanggu village. The sampling technique used a total sampling technique of 80 cadres. Data collection has been done through filling out a questionnaire about stunting prevention. The questionnaire has been measured for validity and reliability tests which are declared valid based on the Guttman scale because the Kr value is> 0.90 and reliable because Ks> 0.60. The data obtained has been analyzed using categorical univariate analysis which will then be analyzed comparatively using the Mann-Whitney analysis test. The research results showed that health cadres in lowland and highland villages had a high level of knowledge about stunting prevention. However, there were knowledge indicators with low scores, including pregnancy checks, implementation and administration of vitamin A capsules, and interpretation of KMS. Overall, there’s no significant difference between the knowledge of lowland cadres and highland cadres regarding stunting prevention.